(untitled) (Revista horizonte, 2014)
Objective: To compare the effects of cold and heat through physiotherapeutic techniques, thermotherapy and cryotherapy, on the maximum strength of the biceps brachii muscle in subjects with circuit strength training. Methods: 18 healthy subjects between 20 and 35 years old belonging to the Energy Fitness gym and Club Balthus of the metropolitan region, who perform functional training 5 times a week, for a period greater than or equal to 3 months, the subjects were selected non-probabilistically by convenience. The evaluation was performed by strength assessment through a biceps brachii curl on Scott bench with dumbbell. Three measurements were performed, with an interval of three days of rest. The first measurement evaluated the maximum strength of the subjects under normal conditions, the second with the application of thermotherapy, through Infrared A, and the third with the application of cryotherapy, using Cryoflow equipment. Results: With the application of Infrared, maximum strength increased significantly (16.8 kg vs. 17.0 kg; P<0.05). With the application of Cryoflow the force decreased significantly (16.8 kg vs. 15.9 kg; P< 0.05). Conclusion: With the application of heat, through Infrared A, the force increased significantly by 1.55%. With the application of cold, through Cryoflow, the maximum force decreased significantly by 4.94%.